Transforming a US scholarly concentrations program internationally: lessons learned - KÜÇÜKDURMAZ, FATİH (BMC, 2019)
BackgroundScholarly Concentrations programs in U.S. medical schools aim to instill passion for critical thinking and promote careers in academic medicine. The rise of these programs has seen variable goals, structure, and outcomes. Transformation of these programs internationally is in its infancy.MethodsWe describe implementation of the Johns Hopkins School of Medicine Scholarly Concentrations program, offering Basic Science, Clinical Science, Medical Ethics/Healing Arts, History of Medicine, and Public Health/Community Service, at Bezmialem Vakif University in Istanbul, Turkey. Over six modules in the preclinical years, students develop a faculty-mentored experience which encourages the acquisition of attitudes and skills for self-directed, lifelong learning and scholarship. This culminates in abstract and project presentation. We report program characteristics (context and logistics) and outcomes (student engagement and experiences).ResultsThe Scholarly Concentrations program at Bezmialem began in 2014, with nearly two completed cohorts of students. In comparison to Johns Hopkins, students at Bezmialem begin at an earlier age (thus do not have as much prior research experience) and are subsequently evaluated for residency in terms of test scores rather than scholarship and publications, but have a similar level of intellectual curiosity and desire to take ownership of their project. Eighty-two percent of Bezmialem students stated the project they pursued was either their own idea or was an idea they formed after meeting with their mentor. Students at Bezmialem were more likely to choose Clinical Science projects (p=0.009). Only 5% of Bezmialem students in end-of-course survey felt dissatisfied with the level of ownership they experienced with their project, a frequency similar to that seen by Johns Hopkins students (2%).ConclusionsScholarly Concentrations programs play an important role in U.S. medical schools, and these programs can be successfully implemented internationally. The Scholarly Concentrations program at Johns Hopkins has been transformed to a program at Bezmialem in Istanbul, the first program outside North America or the European Union. When designing these programs, one must consider the context, logistics, student engagement, and outcomes. While long-term outcomes are needed, this can serve as a model for implementation elsewhere.
Keywords: Scholarly concentrations program; Medical student; International education; MEDICAL-STUDENTS; SCHOOL